2017
DOI: 10.1186/s13024-017-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of LRRK2 binding partners reveals interactions with multiple signaling components of the WNT/PCP pathway

Abstract: BackgroundAutosomal-dominant mutations in the Park8 gene encoding Leucine-rich repeat kinase 2 (LRRK2) have been identified to cause up to 40% of the genetic forms of Parkinson’s disease. However, the function and molecular pathways regulated by LRRK2 are largely unknown. It has been shown that LRRK2 serves as a scaffold during activation of WNT/β-catenin signaling via its interaction with the β-catenin destruction complex, DVL1-3 and LRP6. In this study, we examine whether LRRK2 also interacts with signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 121 publications
2
53
1
Order By: Relevance
“…Web-available mass spectrometry data sets have shown that LRRK2 interacts with the paraspeckle proteins NONO and SFPQ (41, 42), suggesting that the LRRK2 protein may also be sequestered in nuclear paraspeckles, in a manner similar to that of other proteins (21). Although LRRK2 mRNA and protein levels did not change significantly in NEAT1-depleted HEK-293T cells (see qPCR and Western blot in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Web-available mass spectrometry data sets have shown that LRRK2 interacts with the paraspeckle proteins NONO and SFPQ (41, 42), suggesting that the LRRK2 protein may also be sequestered in nuclear paraspeckles, in a manner similar to that of other proteins (21). Although LRRK2 mRNA and protein levels did not change significantly in NEAT1-depleted HEK-293T cells (see qPCR and Western blot in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Coimmunoprecipitation (co-IP) assays were carried out as described previously (11,12). Briefly, total protein from HCT116 cells ($5 Â 10 6 /reaction) stably transfected with TTPAL (Flagtagged) expression vector or empty vector was extracted in radioimmunoprecipitation assay (RIPA) buffer supplemented with proteinase inhibitor (Novagen).…”
Section: Coimmunoprecipitation and Liquid Chromatography-mass Spectromentioning
confidence: 99%
“…Recently, Berwick et al [52] reported that the primary role of LRRK2 in the canonical Wnt signaling pathway is β-catenin repression: loss of LRRK2 increases Wnt/β-catenin activity, whereas overexpressed LRRK2 binds and represses β-catenin. Another study assessing the effect of LRRK2 on Wnt/planar cell polarity (PCP) signaling indicated that LRRK2 activates this pathway via interactions with multiple Wnt/PCP signaling components [53]. These opposing effects suggest that LRRK2 regulates the balance between the Wnt/β-catenin and Wnt/PCP signaling pathways depending on its binding partner.…”
Section: Lrrk2 Mutations and Their Mechanisms Of Actionmentioning
confidence: 99%